The Comuna Universal: Trincadist Spiritism and the Mexican Revolution - Galicia, Alejandra Gabriela (2024)
In the studies on Western Esotericism in Latin America there are few analyses that deal with the Escuela Magnético Espiritual de la Comuna Universal, and the references to the spiritualist school headed by Joaquín Trincado are characterized by being succinct and hagiographic. This paper is a first approach to Trincado's spiritualist proposal, which aims to show the theoretical and political complexity of an occultist proposal elaborated from a Hispanophile point of view.